Pengembangan Media Aqidah Learning Berbasis Hyperlink pada Mata Pelajaran Aqidah Akhlak di MTs Al-Azhar Jombang - Rohmah, Hidayatur; Faizza, Adinda Yulia Nur (YASIN, 2025)
The main issue in Aqidah Akhlak learning at MTs Al-Azhar Peterongan Jombang lies in the prolonged and monotonous lecture method, which lowers students' interest and motivation. There is a strong need for engaging and easy-to-use learning media to increase student engagement. This study aims to develop and evaluate the feasibility of Hyperlink-Based Aqidah Learning media to improve the quality of Aqidah Akhlak learning. The research used a Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects were 30 eighth-grade students. Data collection instruments included observation, interviews, documentation, and questionnaires. Validation results from material experts scored 87% and 100%, while media expert validation scored 97% from each validator. Student response questionnaires scored 91.3%, indicating that the media was categorized as "very engaging." The study concludes that the developed hyperlink-based media is highly feasible and engaging for use in Aqidah Akhlak learning. The implication of this study is that technology-based media can serve as an alternative solution to overcome students' learning boredom and enhance the effectiveness of contextual and interactive religious education.